Relative contributions of plant traits and soil microbial properties to mountain grassland ecosystem services. (21st December 2012) - Grigulis, Karl; Lavorel, Sandra; Krainer, Ute; Legay, Nicolas; Baxendale, Catherine; Dumont, Maxime; Kastl, Eva; Arnoldi, Cindy; Bardgett, Richard D.; Poly, Franck; Pommier, Thomas; Schloter, Michael; et al.
Abstract : Summary: Plant functional diversity and soil microbial community composition are tightly coupled. Changes in these interactions may influence ecosystem functioning. Links between plant functional diversity, soil microbial communities and ecosystem functioning have been demonstrated in experiments using plant monocultures and mixtures, using broad plant and microbial functional groups, but have not been examined in diverse natural plant communities. We quantified the relative effects of plant and microbial functional properties on key ecosystem functions. We measured plant functional diversity, soil microbial community composition and parameters associated with nitrogen (N) cycling and key nutrient cycling processes at three grassland sites in different parts of Europe. Because plant structure and function strongly influence soil microbial communities, we determined relationships between ecosystem properties, plant traits and soil community characteristics following a sequential approach in which plant traits were fitted first, followed by the additional effects of soil micro‐organisms. We identified a continuum from standing green biomass and standing litter, linked mostly with plant traits, to potential N mineralization and potential leaching of soil inorganic N, linked mostly with microbial properties. Plant and microbial functional parameters were equally important in explaining % organic matter content in soil. A parallel continuum ran from plant height, linked with above‐ground biomass, to plant quality effects captured by the leaf economics spectrum, which were linked with the recycling of carbon (C) and N. More exploitative species (higher specific leaf area, leaf N concentrations and lower leaf dry matter content) and taller swards, along with soil microbial communities dominated by bacteria, with rapid microbial activities, were linked with greater fodder production, but poor C and N retention. Conversely, dominance by conservative species (with opposite traits) and soil microbial communities dominated by fungi, and bacteria with slow activities, were usually linked with low production, but greater soil C storage and N retention. Synthesis – Grassland production, C sequestration and soil N retention are jointly related to plant and microbial functional traits. Managing grasslands for selected, or multiple, ecosystem services will thus require a consideration of the joint effects of plant and soil communities. Further understanding of the mechanisms that link plant and microbial functional traits is essential to achieve this. Abstract : Grassland production, C sequestration and soil N retention are jointly related to plant and microbial functional traits. Managing grasslands for selected, or multiple, ecosystem services will thus require a consideration of the joint effects of plant and soil communities. Further understanding of the mechanisms that link plant and microbial functional traits is essential to achieve this.